(untitled) (Bangladesh Journal of Botany, 2025)
A study was conducted to assess the water quality of the Buriganga River, focusing on bacterial screening, antimicrobial activity, and cytotoxicity effects. The bacterial load was significantly high, whereas pH levels were satisfactory. Out of 65 bacterial colonies 5 isolates were provisionally identified as Bacillus sp., Aeromonas sp., Bacillus subtilis, B. cereus, and Enterobacter aerogenes exhibiting antimicrobial activity against six pathogenic food bacteria. Based on the 16S rRNA gene sequencing method, 3 bacterial isolates were identified as Enterobacter sp., Priestia aryabhattai, and Klebsiella pneumoniae. In the cytotoxicity test, these 5 isolates revealed no toxic effects on HeLa and Vero cell lines. Biochemical tests revealed the presence starch, casein, and pectinase. Bangladesh J. Bot. 54(3): 563-569, 2025 (September)